Iluminasi sebagai Sistem Penyajian Konten Cetak (Studi Kasus Iluminasi Injil Abad Ke-15) - Haris Mustafa; Alvanov Zpalanzani Mansoor; Naomi Haswanto (Wimba : Jurnal Komunikasi Visual, 2011)
Illumination is visual decoration in form of coloured fonts, designed or illustrated page in print media. In middle age bibles or manuscripts, there are forms and type of illuminations that may applied as a system of content delivery in books. A framework of illumination design methodology may elaborated through content analysis on several illuminations in bibles and religious manuscripts. This research will enrich visual communication design study, especially typography and illustration study in developing an information system delivery based on visual elements.